Beyond the podium : - Rossett, Allison (Jossey-Bass/Pfeiffer, 2001)
The digital age is infiltrating the training profession faster than most of us can stay breast of it. Beyond the Podium, winner of the ISPI Book Award, will get you up to speed while also refreshing your understanding of the fundamentals. With a focus on the questions you're asking, Rossett and Sheldon open your eyes to the possibilities that are emerging--or already exist--as organizations move into new technologies and performance improvement. They examine the opportunities presented by e-learning, informal learning, independent learning, knowledge management, globalization, object-oriented design, wireless technologies, and more; while revisiting what makes great training, how to do an analysis, and evaluation strategies and tools.